2022
DOI: 10.48550/arxiv.2201.09599
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A lexicographic maximin approach to the selective assessment routing problem

Abstract: Max-min approaches have been widely applied to address equity as an essential consideration in humanitarian operations. These approaches, however, have a significant drawback of being neutral when it comes to solutions with the same minimum values. These equivalent solutions, from a max-min point of view, might be significantly different. We address this problem using the lexicographic maximin approach, a refinement of the classic max-min approach. We apply this approach in the rapid needs assessment process, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 37 publications
(43 reference statements)
0
6
0
Order By: Relevance
“…In this study, we extend the literature on humanitarian relief by considering both bi-objectives and uncertainty of travel times during the RNA stage, which addresses the two conflicting objectives of minimizing the total route duration and maximizing the vector of coverage ratio during the RNA stage. Specifically, we extend the study by Hakimifar et al [15] by investigating the impact of different levels of travel-time uncertainty on the Pareto frontier and the impact on route infeasibility. We apply robust optimization to tackle travel-time uncertainty.…”
Section: Related Literaturementioning
confidence: 93%
See 4 more Smart Citations
“…In this study, we extend the literature on humanitarian relief by considering both bi-objectives and uncertainty of travel times during the RNA stage, which addresses the two conflicting objectives of minimizing the total route duration and maximizing the vector of coverage ratio during the RNA stage. Specifically, we extend the study by Hakimifar et al [15] by investigating the impact of different levels of travel-time uncertainty on the Pareto frontier and the impact on route infeasibility. We apply robust optimization to tackle travel-time uncertainty.…”
Section: Related Literaturementioning
confidence: 93%
“…MDLS provides an approximation of Pareto-optimal solutions by generalizing the concept of local search to multiple objectives [23]. Hakimifar et al [15] compared the performance of the MDLS method with methods previously applied to the SARP and showed that the designed MDLS finds the same max-min coverage ratio in most of the runs and, in some cases, a value that is even higher than the previously best-known value. To apply MDLS, for each objective, we use specific Adaptive Large Neighborhood Search (ALNS) operators, which are introduced and detailed in Hakimifar et al's [15] paper, to lead our search towards better solutions.…”
Section: Solution Methodsmentioning
confidence: 99%
See 3 more Smart Citations